PTH-038 Findings on Back-To-Back Colonoscopies: An Auditable Standard for Colonoscopy Quality?. (4th June 2013) - Vaughan-Shaw, P G; Rai, P; Goodman, A; Valori, R; Aung, M
Abstract : Introduction: An important marker of colonoscopy quality is detection of pathology and incidence of missed pathology. Back-to-back colonoscopies cannot ethically be performed for quality assurance alone yet may be required for clinical reasons. This study aims to investigate the incidence of new findings in colonoscopies repeated within a 12 month period. Methods: All colonoscopies performed over a 3-year period at an Endoscopy training unit were studied. Colonoscopies repeated within a 12-month period were included. Repeats following incomplete colonoscopy were excluded. Data on indication and outcome were collected. Results: 5747 colonoscopies were performed over the study period. 137 repeat colonoscopies were included with median interval 174 days and indications including requirement for endoscopic mucosal resection (n = 47), inflammatory bowel (n = 13) or polyp surveillance (n = 37), previous imaging or endoscopic abnormalities (n = 15), and persistent or new symptoms (n = 25). 19 (14%) repeat colonoscopies yielded new findings including 1 new cancer, 234 days following a normal colonoscopy. Additional polyps were identified in 13 colonoscopies indicating a missed polyp rate of 9%. A median number of 2 polyps per colonoscopy with median size 5.5mm were found. Crohn's disease (n = 1), and diverticular disease (n = 3) were also diagnosed at repeat colonoscopy. There was no morbidity associated with repeat colonoscopy in this series. Conclusion: New pathology was identified in 14% of repeat colonoscopies. Analysis of clinically indicated repeat colonoscopies and rate of detection of new pathology may offer utility in colonoscopy quality assurance. Larger studies are required to define and validate this criterion as an auditable standard for colonoscopy quality. Disclosure of Interest: None Declared.